Les Magasins généraux : de spot à vandales à spot publicitaire ? - Constance Ananos (EchoGéo, 2018)
This paper focuses on a study case of the renovation of an industrial building, the Magasins généraux in Pantin, a suburban city bordering the French capital and belonging to the Seine-Saint-Denis department (93). Due to the deindustrialisation process, the industrial activites in the building were shut down in 2001 and it became an industrial wasteland. From 2004, it was invested by graffiti and street artists to then be transformed in what it is today : a cultural centre managed by the advertising company BETC Paris. During the transformation, graffiti and street art were used as tools both to promote the territory and the agency settling in the building. By their presence in and invasion of the building, they gave it a symbolical value. Such value has been turned into a strategic mercantile one to legitimate the implantation of this original actor on the metropolis scale and to promote a socio-economic model based on the concept of the creative city.